The Impact of Recent Technologies on Smart Emergency Hospitals (Journal of Engineering, 2025)
Smart emergency hospitals constitute a transformative model that addresses the continual challenges of traditional healthcare systems, together with delayed reaction times, elevated clinical errors, and inefficient resource utilization via the combination of superior technologies, which include Artificial Intelligence (AI), the Internet of Things (IoT), and scientific robotics. Despite the growing body of research on medical and administrative benefits, confined interest has been paid to the architectural and spatial implications of this technology. This examines objectives to discover how clever technologies influence the architectural layout of emergency hospitals, particularly in terms of spatial configuration, operational flow, environmental excellence, and versatility. By using a descriptive-analytical technique and referencing benchmark case studies, which include the Beijing Medical Innovation Hospital and Shanghai Smart Hospital, the studies evaluate performance signs based totally on a comparative framework with traditional hospitals of comparable size and function. Key findings screen that smart hospitals have achieved a seventy 5% discount in common emergency response time (from 20 to 5 mins), a 25% development in diagnostic accuracy via AI-assisted imaging, and a 20% increase in useful resource allocation efficiency due to automatic garage and logistics structures. Moreover, operational costs have been reduced by about 33% as compared to standard structures, normally due to automation and virtual optimization. The research concludes that the integration of smart technologies no longer best improves operational performance and affects person pleasure but additionally necessitates a rethinking of emergency health center design to aid adaptive, information-driven, and technology-responsive areas. This highlights the significance of aligning architectural layout with digital transformation techniques and making sure non-stop team of workers schooling and overall performance assessment for lengthy-time period sustainability.